Effect of Bifidobacterium breve in Combination With Different Antibiotics on Clostridium difficile - Yang, Jingpeng; Yang, Hong (Frontiers in Microbiology, 2018)
While combinations of probiotics with antibiotics have exhibited beneficial and adverse effects in the treatment of Clostridium difficile infection (CDI), no substantive explanation has been provided for these effects. In this study, C. difficile ATCC 9689 (CD) was treated with Bifidobacterium breve (YH68) in combination with five different antibiotics to explore the effects of the different combinations on C. difficile. Cell-free culture supernatant (CFCS) of YH68 was combined with metronidazole (MTR), vancomycin (VAN), clindamycin (CLI), ceftazidime (CAZ) or ampicillin (AMP) to treat CD. The plate counting method was used to determine the growth and spore production of CD, and cell damage was assessed by the measurement of extracellular ATP levels with a luminescence-based kit. The production of toxin A/B was measured with an ELISA kit. The gene expression levels of tcdA and tcdB in CD were evaluated by real-time qPCR. The CFCS of YH68 (3×109 CFU/mL) at 0.25 times the minimal inhibitory concentration (MIC) (0.25YH68) in combination with the five antibiotics exerted stronger inhibitory effects on the growth and spore production of CD than the same antibiotics in the absence of 0.25YH68, except 0.25YH68&MTR&AMP, 0.25YH68&MTR&CAZ, and 0.25YH68&VAN&CLI. However, treatment with 0.25YH68&VAN, 0.25YH68&AMP, 0.25YH68&MTR&CAZ, 0.25YH68&VAN&CAZ, 0.25YH68&VAN&AMP, and 0.25YH68&CAZ&AMP resulted in increased cell damage. In addition, the different combinations, except 0.25YH68&CLI, 0.25YH68&MTR&AMP and 0.25YH68&VAN&CLI, dramatically reduced the production of toxin A/B in comparison with the effects of the same antibiotics in the absence of 0.25YH68. The gene expression levels of tcdA and tcdB in CD were lowered upon treatment with 0.25YH68 in combination with MTR, CLI, CAZ, MTR&CAZ, MTR&AMP, CLI&CAZ and CLI&AMP, whereas the levels were enhanced by 0.25YH68 in combination with VAN, AMP, MTR&CLI, VAN&CLI, VAN&AMP and CAZ&AMP. In summary, YH68 in combination with specific antibiotics could enhance the inhibitory effects of antibiotics against CD. In addition, the antagonistic effects between some antibiotics could be weakened by YH68.